Adopting improved farm technology: a study of smallholder farmers in Eastern Province, Zambia - Celis, Rafael; Milimo, John T.; Wanmali, Sudhir (International Food Policy Research Institute, 1991)
In late 1985, the International Food Policy Research Institute in collaboration with the Rural Development Studies Bureau of the University of Zambia, the National Food and Nutrition Commission, and the Easter Provice Agricultural Development Project embarked on a major research project in Eastern Province, Zambia. The study sought to obtain a better understanding of the public policies that govern the country's push to increase agricultural production and improve the participation of smallholder farmers in it. In particular, the study aimed to assess the impact that agricultural technology has on productivity, use and distribution of land, agricultural and rural employment both on and off farms, level and distribution of income, and nutrition status and welfare of the rural population.